Impaired sensitivity to thyroid hormones is associated with high lipoprotein(a) level in euthyroid patients with type 2 diabetes mellitus - Zhong, Luojing; Lin, Ruiyu; Cao, Baozhen; Zhong, Wenying; Tu, Mei; Wei, Wen (Frontiers in Endocrinology, 2025)
BackgroundThe relationship between thyroid hormone sensitivity and lipoprotein(a) (Lp(a)) is unclear. The purpose of this study is to illuminate the correlation between thyroid hormone sensitivity and Lp(a) in euthyroid patients with type 2 diabetes mellitus (T2DM).MethodA cross-sectional study was conducted on 1097 patients with T2DM. The thyroid hormone sensitivity indices, the thyroid feedback quantile-based index (TFQI), the thyroid-stimulating hormone index (TSHI), the thyrotrophic T4 resistance index (TT4RI), and the free triiodothyronine(FT3)/free thyroxine (FT4) ratio were calculated. Linear and binary logistic regression analysis were performed to assess the relationship between thyroid hormone sensitivity indices and Lp(a). Restricted cubic splines were also used to evaluate the association between thyroid hormone sensitivity indices and Lp(a).ResultAmong the 1097 participants, the percentage of Lp(a)≥30 mg/dL was 20.3%. Linear regression analysis revealed that TFQI displayed a positive correlation with Lp(a) levels, whereas the FT3/FT4 ratio exhibited a negative correlation. The adjusted odds ratio (aOR)(95% confidence interval(CI)) for high Lp(a) level was increased with rising TFQI quartiles(Q3: aOR 1.49,95% CI 1.09-2.06; Q4: aOR 1.74, 95% CI 1.36-2.23) (P<0.05),with Q1 as the reference. By contrast,the aOR(95% CI) for high Lp(a) level was decreased with rising FT3/FT4 ratio quartiles (P<0.05). The robustness of these findings was further confirmed by restricted cubic spline analysis.ConclusionIn euthyroid T2DM patients, decreased sensitivity to thyroid hormones was found to be linked with high Lp(a) level. Screening for thyroid hormone insensitivity and serum Lp(a) levels should be emphasized in euthyroid T2DM patients for early intervention and improved outcomes.